Granulocyte colony-stimulating factor (G-CSF) upregulates β1 integrin and increases migration of human trophoblast Swan 71 cells via PI3K and MAPK activation - Furmento, Verónica A. (2016)
Fil: Furmento, Verónica A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Química y Fisicoquímica Biológicas; Argentina